2020
DOI: 10.1093/tropej/fmaa059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcome of SARS-CoV-2 Infection in Neonates: A Systematic Review

Abstract: Objective The objective of this study is to systematically synthesize the currently available literature on various modes of transmission (congenital, intrapartum, and postpartum), clinical features and outcomes of SARS-CoV-2 infection in neonates. Methods We conducted a comprehensive literature search using PubMed, EMBASE, and Web of Science until 9 June 2020. A combination of keywords and MeSH terms, such as COVID-19, coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
92
3
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 90 publications
4
92
3
10
Order By: Relevance
“…The exact incidence of SARS-CoV-2 infection in neonates is largely unknown. The proportion of SARS-CoV-2 positive neonates in our study was 6.5% as compared to 3.9% in a meta-analysis of 58 neonates [1].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The exact incidence of SARS-CoV-2 infection in neonates is largely unknown. The proportion of SARS-CoV-2 positive neonates in our study was 6.5% as compared to 3.9% in a meta-analysis of 58 neonates [1].…”
Section: Discussioncontrasting
confidence: 72%
“…There is little literature available about the clinical features, outcomes and the mode of transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection in neonates, especially from India. Recently, a meta-analysis has described 58 SARS-CoV-2 positive neonates from across the globe [1]. We present the clinical and laboratory profile of SARS-CoV-2 positive neonates admitted to a tertiary-care public hospital.…”
mentioning
confidence: 99%
“…In children, the immune system is immature [13], thus aggressive cytokine response is rarely seen [28] resulting in milder COVID-19 symptoms. The severity of COVID-19 in children was recently reviewed by two meta-analyses [8,17]. Even though the reviews had large cohorts (7480, 4857 patients), the severity of illness was described only in 20-34% of all patients (1475 and 1666 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Children are mostly asymptomatic or experience much milder symptoms than the adults [1,7,9,12,15,19,21,41], although a low percentage of the infected children developed the pediatric multi-system inflammatory syndrome [34]. Severe (2-3%) or critical illness (0.61%) has been reported in pediatric patients analyzed in two systematic reviews and meta-analysis of data from several countries [8,17]. The purpose of our study was to establish if a lower frequency of infection, and lesser severity in children were also true for the 2020 COVID-19 pandemic in Warsaw, Poland.…”
Section: Introductionmentioning
confidence: 99%
“…However, following the subsequent progression of the pandemic to involve countries in the Western Hemisphere, Europe, and the Middle East, the spectrum of reported clinical manifestations of the infection in pregnancy appeared to worsen, with pregnant women developing severe and critical pneumonia, thrombosis, cardiomyopathy, multiorgan disease, need for intensive care, and mechanical ventilation which, in a small number of cases, resulted in maternal deaths [10][11][12][13]. In addition to reports of increases in maternal morbidity and mortality, there were increasing descriptions of newborn infants who tested positive for SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), the causative agent of COVID-19 [14][15][16][17]. Analysis of pooled data from multiple studies indicated that only a small percentage of neonates delivered to pregnant women with COVID-19 tested positive for the virus [18].…”
Section: Introductionmentioning
confidence: 99%